A review on underwater autonomous environmental perception and target grasp, the challenge of robotic organism capture. (1st January 2020) - Huang, Hai; Tang, Qirong; Li, Jiyong; Zhang, Wanli; Bao, Xuan; Zhu, Haitao; Wang, Gang
Abstract: The worldwide demands for high protein seafood are growing rapidly. Through robots instead of divers completing the capture will not only reduce the cost, but also improve the operation safety. Although a great number of underwater vehicles have been developed, it is still difficult for them to realize agile and uninjured sea organism capturing autonomously. This paper is proposed to investigate the current state of art about underwater autonomous and dexterous operation robot, underwater autonomous environmental perception, underwater vehicle-manipulator system modeling and coordinated control, target uninjured grasp; in order to analyze the difficulties and research methodologies for the robot development of sea organism autonomous and uninjured capture. To make analysis on the organism autonomous capture process, this article has presented two different open frame underwater vehicles, the absorption type one and the grasp type one. Analysis including autonomous visual search and detection process, acceleration-level task priority redundancy resolution approach for trajectory planning and grasp capture. Experiments with the organism autonomous grasp and absorption process have both been purposed. Highlights: On the basis of literature comparison and analysis, the architecture of remotely autonomous robot for organism absorb and grasp has been proposed. The purposed acceleration-level task priority redundancy resolution approach can optimize restoring moments and generate grasp trajectory for motion planning. Experiments with the organism autonomous grasp and absorb have both been purposed.